The Passenger Satisfaction Analysis of Commuter Line in the New-Normal Period - Dimas Pratama; Andri Irfan Rifai; Susanty Handayani (International Journal Labs, 2022)
KRL Commuter Line is an adequate means of public transportation and has a vital role in the activities or activities of the general public in the Jabodetabek area. However, since the Indonesian government declared a state of emergency and the coronavirus outbreak a national disaster due to the spread of the Covid-19 virus in March 2020, it has impacted the service system Commuter Line KRL operations. With the Covid-19 virus, PT Kereta Commuter Indonesia has created a new operational service system to continue providing exemplary service so that KRL Commuter Line service users remain safe and comfortable. Furthermore, PT Train Commuter Indonesia implements regulations and policies following government regulations to stop the spread of Covid-19, such as implementing protocols health of KRL Commuter Line service users, thereby affecting travel patterns. Therefore, the authors want to research the behavior of transportation users on the public KRL Commuter Line in the New Normal Period. The writer also wants to know the public's perception of the applicable health protocol regulations and policies and whether they affect KRL Commuter Line passenger trips.